HUBUNGAN PERMODALAN DENGAN TINGKAT SISA HASIL USAHA (Studi KPRI GIAT KECAMATAN KUTOARJO) - Titik Suhartini (Politeknik Sawunggalih Aji, 2017)
The thesis titled relationship capital with the level of the net income in the district KPRI GIAT Kutoarjo. In this report the authors conducted research on the matter is there a realationship between the amount of the capital gain on KPRI entrirpising business district Kutoarjo as for research purpose will achieved if the correlation is significant or not In this study te authors use two-way hypothesis that the alternative hypothesis that suggested a link between the capital gains rate SHU, the null hypothesis states there is no relationship between the level of capital gain SHU. As for the method that I used in this study is the method of literature, method of observation, interview methods, methods of documentation and data analysis method Obtained from the calculation of the t test t=2,794 and t table and the table = 4,303 so that it can be said that there is no relationship between acquisition of the remaining wguity in the operatin result KPRI GIAT Kutoarjo enterprising district That the hypothesis that states there is a relationship between the capital and the acquisition of the nest income district KPRI enterprising Kutoarjo was rejected due to the acquisition of SHU isnot from capital but from the services of the members of the cooperative Key words: capital, net income